Italian Women’s Resistance to Oppression in the Novel My Brilliant Friend by Elena Ferrante (2011) - Fernando, Harif; Wahyuni, Delvi (English Language and Literature, 2024)
This research discusses resistance to oppression carried out by female characters in the novel My Brilliant Friend (2011) by Elena Ferrante. This research focuses on the types of oppression and resistance that female characters accept and carry out to face male domination. This research uses feminist literary theory with the support of two other theories, namely oppression theory and resistance theory to analyze the novel. The method used in this research is descriptive qualitative. Results of this research divided into 2. First, 3 types of oppression such as marginalization, exploitation, and violence. Second, 2 types of resistance such as open resistance and hidden resistance. The two things above are represented by several characters. First, Lila’s father who represents marginalization, physical violence and psychological violence. Second, Rino, Lila’s brother, represents marginalization and physical violence. Third, Enzo represents physical violence. Fourth, gino represents sexual violence. Fifth, Donato Sarratore, who represents sexual violence and psychological violence. Sixth, the stranger represents marginalization, exploitation and sexual violence. Seventh, Lila which represents open resistance and hidden resistance. Eighth, Lenu represents open resistance and hidden resistance.